Transformation of the Central Leadership Movement of the Islamic Student Association (PP. HIMA PERSIS) for the 2025-2028 Period: A Grand Narrative Model in Building a Powerful and Sustainable Organization - Sholahudin Hasan; Faizal Rizqi Syawalludin; Aldi Surizkika (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
The Islamic student organization movement in Indonesia faces significant challenges amid digital disruption, shifting socio-political landscapes, and economic uncertainty. HIMA PERSIS responds to these challenges by formulating a comprehensive movement concept in its 2025–2028 work program. This article aims to formulate and analyze the grand narrative model of the transformation of the HIMA PERSIS movement as a conceptual framework for building a robust and sustainable organization. This study employs a qualitative approach and analyzes the 2025–2028 HIMA PERSIS Central Leadership concept paper, which is then combined with literature on Islamic social movements, cadre Development, and value-based organizational governance. The analysis shows that the document constructs a grand narrative of transformation across five main pillars: organizational and cadre transformation, research and technology transformation, economic and entrepreneurial transformation, political and social transformation, and international movement transformation. A grand narrative of HIMA PERSIS unites these five pillars as a cadre movement rooted in Islamic values, responsive to changing times, and oriented towards independence and sustainability. This article proposes a conceptual model of the grand narrative that can serve as a reference for strategic planning, strengthening movement identity, and systematic program management. In practical terms, HIMA PERSIS and other Islamic student organizations can use this model to formulate a more integrated, measurable, and globally relevant long-term direction for their movements.